2022
DOI: 10.3390/ijms23052621
|View full text |Cite
|
Sign up to set email alerts
|

The BDNF/TrkB Neurotrophin System in the Sensory Organs of Zebrafish

Abstract: The brain-derived neurotrophic factor (BDNF) was discovered in the last century, and identified as a member of the neurotrophin family. BDNF shares approximately 50% of its amino acid with other neurotrophins such as NGF, NT-3 and NT-4/5, and its linear amino acid sequences in zebrafish (Danio rerio) and human are 91% identical. BDNF functions can be mediated by two categories of receptors: p75NTR and Trk. Intriguingly, BDNF receptors were highly conserved in the process of evolution, as were the other NTs’ re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 131 publications
1
18
0
Order By: Relevance
“…A previous study on zebrafish showed the presence of TrkA and TrkB/BDNF in sensory cells of taste buds [29,30]. In view of this, a local action in zebrafish taste buds could be supposed for NGF as well as for BDNF/NT4 detected in the present study for TrkA and TrkB positive cells, respectively, probably through a paracrine/autocrine mechanism.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A previous study on zebrafish showed the presence of TrkA and TrkB/BDNF in sensory cells of taste buds [29,30]. In view of this, a local action in zebrafish taste buds could be supposed for NGF as well as for BDNF/NT4 detected in the present study for TrkA and TrkB positive cells, respectively, probably through a paracrine/autocrine mechanism.…”
Section: Discussionsupporting
confidence: 69%
“…In fish, neurotrophins are widely represented in the brain [11][12][13][14][15][16][17][18][19] and sensory organs such as the retina [20][21][22][23][24], inner ear, lateral line and olfactory organ [25][26][27]. Previous studies in fish demonstrated the presence of neurotrophin receptors in taste buds (TBs), namely the common Trk amino acid sequence in sea bass [28], while TrkB and TrkA have been reported in zebrafish (Danio rerio) [27,29,30], thus suggesting the sensibility of fish TBs to neurotrophins.…”
Section: Introductionmentioning
confidence: 99%
“…It can promote the growth of neurons, promote the formation and stability of neuronal synapses, as well as promote long-term potentiation . A previous study found that BDNF as well as its receptor TrkB was reduced in patients with depression . BDNF knockout in the DG leads to depression-like behaviors .…”
Section: Discussionmentioning
confidence: 99%
“…45 A previous study found that BDNF as well as its receptor TrkB was reduced in patients with depression. 46 BDNF knockout in the DG leads to depression-like behaviors. 47 In vivo perfusion of hippocampal BDNF can induce antidepressant effects in depressive animals.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The receptors of the nerve growth factor are of two types: low-a nity nerve growth factor (p75NTR, also referred to as NGFR) and high-a nity tyrosine kinase receptor (TrkA) [11]. NGFR has a relatively simple structure and interacts non-speci city with four neurotrophic factors, namely, NT-4, NT-3, Brain-Derived Neurotrophic Factor (BDNF), and Nerve Growth Factor (NGF) [12]. NGFR performs a positive regulatory function in cell survival and proliferation in synergy with TrkA while promoting apoptosis in the absence of TrkA.…”
Section: Introductionmentioning
confidence: 99%